2020
DOI: 10.1021/acsami.0c01167
|View full text |Cite
|
Sign up to set email alerts
|

Gemini Peptide Amphiphiles with Broad-Spectrum Antimicrobial Activity and Potent Antibiofilm Capacity

Abstract: To address the challenge from microbial resistance and biofilm, this work develops three gemini peptide amphiphiles with basic tetrapeptide spacers 12-(Arg)4-12, 12-(Lys)4-12, and 12-(His)4-12 and finds that they exhibit varied antimicrobial/antibiofilm activities. 12-(Arg)4-12 shows the best performance, possessing the broad-spectrum antimicrobial activity and excellent antibiofilm capacity. The antimicrobial and antibiofilm activities strongly depend on the membrane permeation and self-assembling structure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 46 publications
2
40
0
Order By: Relevance
“…All of the CTPs exhibited significant antibiofilm activity and could effectively inhibit biofilm formation of most tested S. aureus strains at sublethal concentrations (1 × MIC), as detected using the crystal violet method (Figure 9). This was consistent with other reports, which suggest that membrane-penetrated peptides may also block the formation of pathogen biofilms [49,50]. C-terminal amidation of the peptides has been reported to enhance its antibiofilm activity [51].…”
Section: Discussionsupporting
confidence: 93%
“…All of the CTPs exhibited significant antibiofilm activity and could effectively inhibit biofilm formation of most tested S. aureus strains at sublethal concentrations (1 × MIC), as detected using the crystal violet method (Figure 9). This was consistent with other reports, which suggest that membrane-penetrated peptides may also block the formation of pathogen biofilms [49,50]. C-terminal amidation of the peptides has been reported to enhance its antibiofilm activity [51].…”
Section: Discussionsupporting
confidence: 93%
“…Similarly to other antibiofilm peptides against human pathogens ( Mishra and Guangshun, 2017 ; Park et al, 2019 ; Qi et al, 2020 ), the antibiofilm activity of BP525 , 1037 , and R-FV7-I16 showed a dose–effect relationship that fitted well with a Michaelis–Menten saturation curve. Interestingly, they showed low ED 50 values, which means that low peptide concentrations already display high antibiofilm activity.…”
Section: Discussionmentioning
confidence: 74%
“…The antibiofilm activity of TZP4 against mature ARPA biofilms was confirmed using CLSM with LIVE/DEAD staining (SYTO9/PI), as previously described 19,20 …”
Section: Methodsmentioning
confidence: 99%